A conceptual graph approach to semantic similarity computation method for e-service discovery. (10th April 2010) - Song, William; Du, Xiaofeng; Munro, Malcolm
E-services are services that make themselves available on the web and can be invoked over the internet. These services can be composed together to form new services. With the great growth of the number of services on the web it is indispensable to adopt an effective and efficient way to discover and compose them to meet the users' requirements. However, current web services description languages such as WSDL and OWL-S do not provide semantic support for automatic search and composition of services. In this paper, based on the Conceptual Graph theory, we propose a contextual based conceptual model for automatic search and match for services using two kinds of contextual information – service characteristics and inter-service semantic relations. We explore the theoretical models for inter-service and service characteristics semantic similarity computation to match users' service queries and based on the conceptual model we present an effective service matching algorithm.